Surgical treatment of common bile duct cysts - N. A. Yaitsky; A. Yu. Korolkov; T. O. Nikitina; D. N. Popov (Вестник хирургии имени И.И. Грекова)
The practice observation is given - surgical treatment of the patient with the cyst of the common bile duct. 34 years old patient was received with complaints of recurrent paroxysmal pain in the upper abdomen, nausea, vomiting, chills and fever up to 39 оС. During the process of examination, the cyst of the common bile duct was detected. The following procedures were performed for the patient: laparotomy, cyst of the common bile duct resection, Roux-en-Y bilio - jejuna anastomosis, Felker drainage.